Hedging Effectiveness on the MISO Exchange - Jones, Kevin (International Journal of Energy Economics and Policy, 2024)
The purpose of this paper is to evaluate the effectiveness of four commonly used hedging techniques on wholesale electricity prices within the Midcontinent Independent System Operator (MISO) energy market. This analysis provides and in-depth assessment of hedging performance on one of the largest power markets in North America. In a break from extant literature, hourly time series are used to create hedge portfolios for each of the regional hubs within the MISO footprint. Each risk management strategy is employed on 24 hourly time series for each of the eight regional hubs within the MISO footprint. This results in a total of 768 hedged portfolios across 192 hourly time series. While the naïve approach tends to outperform the others in terms of variance reduction, none of the strategies examined meet the generally accepted standard for a highly effective hedge. In several instances, the hedged portfolio contains a higher amount of risk than the unhedged position. This may be explained by the unique characteristics of wholesale electricity and hedging pressure, particularly during peak demand hours.